STUDI ANALISIS KUALITAS AIR SUNGAI BAH BIAK KOTA PEMATANGSIANTAR - Handoco, Ewin (TRITON: Jurnal Manajemen Sumberdaya Perairan, 2021)
High community activity on the border of the Bah Biak River causes pollution in the waters of the river. The increase in the number of settlements and industries in Pematangsiantar city certainly has an impact on the quality of its waters. The purpose of this study is to find out the water quality of the Bah Biak River in Pematangsiantar City covering the physical and chemical parameters of the waters. This research was conducted in 2021 in Bah Biak River Pematangsiantar city. Water sampling in the Bah Biak River is carried out with three repetitions, namely in March, June and August taking into account the representation of the seasons. Water sampling is carried out in situ for parameters of brightness, pH, total dissolved solid (TDS), electrical delivery, temperature and dissolved oxygen (DO), ammonia, while for laboratory scale measurements are carried out for biologycal oxygen demand (BOD) and chemical oxygen demand (COD) parameters. The results of the measurement will be displayed in graphic form and descriptively discussed by referring to the specified quality standards. Based on the results of measurements of several water quality parameters in the Bah Biak River, it can be concluded that the majority of the parameters studied still meet the quality standards but there are parameters that have passed the quality standard threshold, namely BOD and ammonia parameters. ABSTRAK Tingginya aktivitas masyarakat di sempadan Sungai Bah Biak menyebabkan pencemaran di perairan sungai tersebut. Peningkatan jumlah pemukiman dan industri di Kota Pematangsiantar tentu berdampak kepada kualitas perairannya. Tujuan penelitian ini adalah untuk mengetahui kualitas air sungai Bah Biak di Kota Pematangsiantar meliputi parameter fisik dan kimia perairan. Penelitian ini dilakukan pada tahun 2021 di Sungai Bah Biak Kota Pematangsiantar. Pengambilan sampel air di Sungai Bah Biak dilakukan dengan tiga kali pengulangan yaitu pada bulan Maret, Juni dan Agustus dengan mempertimbangkan keterwakilan musim. Pengambilan sampel air dilakukan secara insitu untuk parameter kecerahan, pH, total dissolved solid (TDS), daya hantar listrik, suhu dan dissolved oxygen (DO), ammonia, sedangkan untuk pengukuran skala laboratorium dilakukan untuk parameter biologycal oxygen demand (BOD) dan chemical oxygen demand(COD). Hasil pengukuran akan ditampilkan dalam bentuk grafik dan dibahas seacara deskriptif dengan merujuk pada baku mutu yang ditetapkan. Berdasarkan hasil pengukuran beberapa parameter kualitas air di Sungai Bah Biak maka dapat disimpulkan bahwa mayoritas parameter yang diteliti masih memenuhi baku mutu namun terdapat parameter yang telah melewati ambang baku mutu yaitu parameter BOD dan ammonia. Kata Kunci: kualitas air, aktivitas masyarakat, pencemaran, baku mutu, Sungai Bah Biak